2019
DOI: 10.1186/s12883-019-1338-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of QoL in neurofibromatosis patients: a systematic review and meta-analysis study

Abstract: Background The neurofibromatoses (NF) are a group of genetic disorders that interfere negatively with the quality of life (QoL) and influence physical, emotional and social statuses. Studying the effects of neurofibromatoses on various aspects of QoL seems important to implement beneficial strategies in increasing the QoL of NF patients. The aim of this study was to review the literature on quality of life in patients with NF and quantitatively evaluate the effects of Neurofibromatosis on various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…Although the anxiety measures used in this study have not been commonly used in population studies in NF1, the higher rate of anxiety in NF1 is consistent with previous literature [ 18 , 21 ]. Of interest, women with NF1 have previously been shown to display increased psychosocial, physical morbidity and decreased quality of life (QoL) [ 13 , 20 , 21 , 61 ] in contrast to other studies of women at increased breast cancer risk, where QoL scores are closer to the general population [ 38 ]. We propose that heightened anxiety and cancer worry may be related to the reported increased incidence of NF1-specific cognitive and mental health issues, as well as the poorer QoL associated with the condition [ 62 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the anxiety measures used in this study have not been commonly used in population studies in NF1, the higher rate of anxiety in NF1 is consistent with previous literature [ 18 , 21 ]. Of interest, women with NF1 have previously been shown to display increased psychosocial, physical morbidity and decreased quality of life (QoL) [ 13 , 20 , 21 , 61 ] in contrast to other studies of women at increased breast cancer risk, where QoL scores are closer to the general population [ 38 ]. We propose that heightened anxiety and cancer worry may be related to the reported increased incidence of NF1-specific cognitive and mental health issues, as well as the poorer QoL associated with the condition [ 62 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits normally manifest as mild intellectual impairment, learning difficulties or attentional difficulty [ 14 , 19 ], with 8% of individuals with NF1 intellectually disabled [ 19 ]. As NF1 impacts physical, cognitive and psychological functioning, it has been reported to have an adverse effect on quality of life [ 20 ]. It is also associated with higher rates of anxiety and depression than the general population, with anxiety and/or depressive symptoms identified in more than half of those from two adult NF1 cohorts [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indications of higher levels of anxiety can contribute to lower QoL 6,8 ; however, more research is needed to evaluate how the barriers of employment can affect generalized anxiety. A recent metaanalysis concluded that QoL affects the well-being of the individual because of the impact onto physical, emotional, and cognitive functioning 31 . Looking at aggregate values, total barriers of employment were signi cantly higher for the control group than individuals with NF1, providing that while barriers such as physical, mental, social and societal pressures are constrained on individuals with NF1, the perception of work barriers may be perceived as secondary from a QoL perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Children with NF1 have an impaired quality of life (QoL) 2,3 . Neuropsychological and learning disorders are also frequent complications in these children (30-65% 4 ), especially when they involve executive functions (EFs) 5,6 .…”
Section: Introductionmentioning
confidence: 99%